Improving prescribing practices with rapid diagnostic tests (RDTs): synthesis of 10 studies to explore reasons for variation in malaria RDT uptake and adherence. Issue 3 (8th March 2017) - Burchett, Helen E D; Leurent, Baptiste; Baiden, Frank; Baltzell, Kimberly; Björkman, Anders; Bruxvoort, Katia; Clarke, Siân; DiLiberto, Deborah; Elfving, Kristina; Goodman, Catherine; Hopkins, Heidi; Lal, Sham; et al.
Abstract : Objectives: The overuse of antimalarial drugs is widespread. Effective methods to improve prescribing practice remain unclear. We evaluated the impact of 10 interventions that introduced rapid diagnostic tests for malaria (mRDTs) on the use of tests and adherence to results in different contexts. Design: A comparative case study approach, analysing variation in outcomes across different settings. Setting: Studies from the ACT Consortium evaluating mRDTs with a range of supporting interventions in 6 malaria endemic countries. Providers were governmental or non-governmental healthcare workers, private retail sector workers or community volunteers. Each study arm in a distinct setting was considered a case. Participants: 28 cases from 10 studies were included, representing 148 461 patients seeking care for suspected malaria. Interventions: The interventions included different mRDT training packages, supervision, supplies and community sensitisation. Outcome measures: Analysis explored variation in: (1) uptake of mRDTs (% febrile patients tested); (2) provider adherence to positive mRDTs (% Plasmodium falciparum positive prescribed/given Artemisinin Combination Treatment); (3) provider adherence to negative mRDTs (% P. falciparum negative not prescribed/given antimalarial). Results: Outcomes varied widely across cases: 12–100% mRDT uptake; 44–98% adherence to positive mRDTs; 27–100% adherence to negative mRDTs. Providers appeared more motivated to perform well when mRDTs and intervention characteristics fitted with their own priorities. Goodness of fit of mRDTs with existing consultation and diagnostic practices appeared crucial to maximising the impact of mRDTs on care, as did prior familiarity with malaria testing; adequate human resources and supplies; possible alternative treatments for mRDT-negative patients; a more directive intervention approach and local preferences for ACTs. Conclusions: Basic training and resources are essential but insufficient to maximise the potential of mRDTs in many contexts. Programme design should respond to assessments of provider priorities, expectations and capacities. As mRDTs become established, the intensity of supporting interventions required seems likely to reduce.